Enhancing SAPF performance with VOC and SVM for electrical networks depollution - Bayoude, Kamal; Moutchou, Mohamed; Zahraoui, Yassine (Institute of Advanced Engineering and Science, 2026)
This paper presents a significant enhancement in the filtering performance of shunt active power filters (SAPF) by leveraging the voltage oriented control(VOC) in combination with a three-level NPC inverter using space vector modulation (SVM). The VOC technique enables precise control of the SAPF by utilizing the orientation of the voltages, thereby optimizing harmonic compensation and reference tracking. Incorporating a three-level inverter allows for more refined voltage modulation, resulting in a substantial reduction in injected harmonic content. Simulation results from MATLAB/Simulink demonstrate the effectiveness of this approach. Before compensation, the measured total harmonic distortion (THD) reaches 27.98%, exceeding the IEEE 519-1992 standard threshold of 5%. However, after applying the SAPF, the THD drops to 0.85%, aligning with international standards for power quality. The figures included in the study illustrate the stability of the phase-locked loop(PLL)voltages and the noticeable improvement in the source current waveforms, which exhibit a near-sinusoidal profile after filtering. These findings validate the superiority of the VOC strategy coupled with an NPC inverter and SVM in effectively mitigating harmonic distortions and enhancing power quality in modern electrical networks.